Local Government’s Role in Bridging Investment Disparities in Indonesia: A Sustainable Development Goals Perspective - Haiti, Rudolf; Situmeang, Ampuan; Tan, Winsherly (Journal of Judicial Review, 2024)
The decentralization within Indonesia's governmental system was established to facilitate equitable development and economic growth by devolving authority to local governments that better understand their region's potential and challenges. An integral aspect of achieving development and economic growth parity lies in investment, an arena still marred by disparities across various regions in Indonesia. This normative study, employing a legal approach to legislation, aims to analyze the legal issues influencing investment disparities, which in turn affect the implementation of SDGs in Indonesia. The analysis reveals limitations faced by local governments in providing incentives and support to attract investment due to their lack of authority in pioneering industries, which are also not linked to the local economy. Additionally, there exists legal uncertainty surrounding local government collaborations with external parties, particularly in the context of investment. These findings reflect a regulatory framework in Indonesia that fundamentally diverges from the spirit of decentralization enshrined in the constitution.